AC losses in Sn-doped Bi1.6Pb0.4Sr2(Ca1-xSnx)2Cu3Oδ superconductors - Hashim @ Ismail, Azhan; Shaari, Abdul Halim; Ahmad @ Muhamad, Nazree; Kassim, Azman; Senawi, Syamsyir Akmal (Trans Tech Publications, 2014)
Measurements of complex AC susceptibility χ = χ + χ as a function of temperature have been carried out on Sn-doped Bi1.6Pb0.4Sr2(Ca1-xSnx)2Cu3Oδ superconductor samples prepared via the conventional solid state reaction method. All the samples exhibit perfect diamagnetism below 109 K. The χ (T) curves display two-step features, indicating the presence of mixed phases and therefore weakening of the grains' coupling. The amount of shielded volume in Sn-free samples is greater than that in Sn-doped samples. The intrinsic peak due to the small AC losses within the grain was not observed in the χ (T) curves for all samples. However, the coupling peak, TP, for Sn-free samples at an applied field of 1.0 Oe was observed at 89 K and shifted to a lower temperature ranging from 59 K to 64.2 K in Sn-doped samples. The amounts of hysteresis losses above the TP in all doped samples were smaller than that of the Sn-free sample. Therefore, the effect of Sn doping suppressed the inter-granular critical current, Jcm, and the presence of weak links that coupled the superconducting grains.